2011
DOI: 10.1021/ol200267b
|View full text |Cite
|
Sign up to set email alerts
|

Palladium- and Nickel-Catalyzed Aminations of Aryl Imidazolylsulfonates and Sulfamates

Abstract: A nickel complex derived from dppf, along with NaOt-Bu as the base, allowed for challenging aminations of aryl sulfamates. An improved functional group tolerance is observed in novel palladium-catalyzed aminations of imidazolylsulfonates with rac-BINAP as the ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 54 publications
1
53
0
5
Order By: Relevance
“…Ethyl‐4‐anilinobenzoate : cololess solid; mp 109.1–109.4 °C (lit . 111 °C); IR (neat) 582, 693, 750, 768, 806, 845, 960, 1019, 1109, 1173, 1249, 1271, 1334, 1364, 1407, 1475, 1495, 1528, 1587, 1676, 1687, 2965, 3338, 3365; 1 H NMR (400 MHz, CDCl 3 ), δ=1.38 (t, 3H), 4.33 (q, 2H), 7.00 (d, 2H), 7.06 (t, 1H), 7.17 (d, 2H), 7.33 (t, 2H), 7.92 (d, 2H); 13 C NMR (100 MHz, CDCl 3 ) δ=14.4, 60.4, 114.5, 120.2, 121.3, 123.0, 129.4, 131.3, 140.9, 148.0, 166.5.…”
Section: Methodsmentioning
confidence: 99%
“…Ethyl‐4‐anilinobenzoate : cololess solid; mp 109.1–109.4 °C (lit . 111 °C); IR (neat) 582, 693, 750, 768, 806, 845, 960, 1019, 1109, 1173, 1249, 1271, 1334, 1364, 1407, 1475, 1495, 1528, 1587, 1676, 1687, 2965, 3338, 3365; 1 H NMR (400 MHz, CDCl 3 ), δ=1.38 (t, 3H), 4.33 (q, 2H), 7.00 (d, 2H), 7.06 (t, 1H), 7.17 (d, 2H), 7.33 (t, 2H), 7.92 (d, 2H); 13 C NMR (100 MHz, CDCl 3 ) δ=14.4, 60.4, 114.5, 120.2, 121.3, 123.0, 129.4, 131.3, 140.9, 148.0, 166.5.…”
Section: Methodsmentioning
confidence: 99%
“…Ackermann and coworkers found that the catalyst system composed of Ni(cod) 2 /dppf was suitable for the amination of aryl sulfamates with anilines and problematic primary alkyl amines 54. Reactions proceeded efficiently at 105 °C in the presence of NaO t Bu with 5 mol% catalyst.…”
Section: Amination Of Phenol‐derived Electrophilesmentioning
confidence: 99%
“…Phenols are typically protected by various groups to enhance their leaving ability in cross-coupling reactions [ 1 , 2 , 3 ]. Thus, phenols have usually been converted to their corresponding aryl C-O electrophiles, such as fluoroalkylsulfonates [ 4 , 5 ], sulfamates [ 6 , 7 , 8 ], sulfonates [ 9 , 10 , 11 , 12 ], carbonates [ 13 , 14 , 15 ], carbamates [ 16 , 17 ], ethers [ 18 ], phosphoramides, phosphonium salts, phosphates, and pivalates [ 19 , 20 , 21 , 22 ]. Besides the preferable availability of phenol derivatives, this method also proves to be cost-effective, as well as an efficient reaction route to form C-C bonds, C-N bonds, and C-H bonds ( Scheme 1 ) [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%